2021
DOI: 10.1145/3432925
|View full text |Cite
|
Sign up to set email alerts
|

Making it Work, or Not

Abstract: Online freelancing is growing rapidly. However, despite this rapid growth, we have a limited understanding of online freelancers' long-term experiences and evolution, or how online freelancing influences freelancers' broader career goals. To address this gap, we interviewed a set of online freelancers at two time periods, two and a half years apart. We found that long-term engagement with online freelancing involves a unique set of financial, emotional, relational, and reputational burdens that represent the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…To better handle this kind of issue, some chose to use public communication channels to gain platform and algorithmic literacy from their global colleagues (Almoqbel & Wohn, 2019). Also, workers joined other digital labor platforms, improving their knowledge about platform design and their knowledge of platform policy and regulations (Blaising et al, 2021). The results of the interviews conducted by Jarrahi and Sutherland (2019) with Upwork gig workers showed that algorithm sensemaking is a sophisticated, strategic, and multistep process that workers need to keep learning.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To better handle this kind of issue, some chose to use public communication channels to gain platform and algorithmic literacy from their global colleagues (Almoqbel & Wohn, 2019). Also, workers joined other digital labor platforms, improving their knowledge about platform design and their knowledge of platform policy and regulations (Blaising et al, 2021). The results of the interviews conducted by Jarrahi and Sutherland (2019) with Upwork gig workers showed that algorithm sensemaking is a sophisticated, strategic, and multistep process that workers need to keep learning.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike workers in traditional organizations who often receive formal job training, gig workers have to figure out the digital workplace and its algorithms on their own (Vasudevan & Chan, 2022), as most platforms only mediate the interactions between clients and workers and do not provide professional training (Blaising et al, 2018). Therefore, knowledge sharing (A23) among gig workers typically occurs through third parties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the "infrastructure supporting individuals' careers in the gig economy is deeply relational in nature" [3], it is important that freelancers accrue portable human capital. After amassing such social capital, workers may maintain their reputation using various strategies such as keeping a high and positive rating, reaching out to past clients or cultivating relational agility by productively forming, maintaining and dissolving work relationships [7,49].…”
Section: Strategies In Online Freelancingmentioning
confidence: 99%